2020
DOI: 10.1124/jpet.120.000080
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase Inhibitor Ensifentrine Reduces Production of Proinflammatory Mediators in Well Differentiated Bronchial Epithelial Cells by Inhibiting PDE4

Abstract: Cystic fibrosis (CF) is caused by mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) anion channel that impair airway salt and fluid secretion. Excessive release of pro-inflammatory cytokines and chemokines by CF bronchial epithelium during airway infection leads to chronic inflammation and a slow decline in lung function, thus there is much interest in finding safe and effective treatments that reduce inflammation in CF. We showed previously that the cyclic nucleotide phosphodiesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 89 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Its pharmacological mechanisms involve reducing inflammatory cytokines production, leukocyte infiltration and phagocytosis at the onset of inflammation (29,30). Besides, the corticosteroid can interfere with the interaction between proinflammatory factors (31,32). Although corticosteroids may cause injury to the infused CAR-T cell and reduce the curative effect, previous studies and our results show that corticosteroids are still very important for the treatment of cytokine storm-related diseases as hemophagocytic syndrome and CRS (33)(34)(35).…”
Section: The Onset Time Of Crs and Administration Time Of Corticosteroids/ Tocilizumab Were Associated With Severity Of Crs And Cardiac Dmentioning
confidence: 69%
“…Its pharmacological mechanisms involve reducing inflammatory cytokines production, leukocyte infiltration and phagocytosis at the onset of inflammation (29,30). Besides, the corticosteroid can interfere with the interaction between proinflammatory factors (31,32). Although corticosteroids may cause injury to the infused CAR-T cell and reduce the curative effect, previous studies and our results show that corticosteroids are still very important for the treatment of cytokine storm-related diseases as hemophagocytic syndrome and CRS (33)(34)(35).…”
Section: The Onset Time Of Crs and Administration Time Of Corticosteroids/ Tocilizumab Were Associated With Severity Of Crs And Cardiac Dmentioning
confidence: 69%
“…Thus, ensifentrine (PDE4 and 3 inhibitor) reduced their secretion in bronchial epithelial cells. This mechanism is exclusively driven by PDE4 [125]. In human alveolar epithelial cells (A549; stimulated with cigarette smoke and LPS), roflumilast and its active metabolite roflumilast N-oxide reduced IL-8 and MCP-1 release and the secretion of CXCL1 [126].…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…They demonstrated that dual inhibition of PDE3 and 4 by ensifentrine diminished the release of proinflammatory mediators, and that this effect was enhanced when ensifentrine was associated to a beta-2 agonist or a glucocorticosteroid. 56 …”
Section: Preclinical Data With Pde3 Pde4 and Dual Pde3/4 Inhibitors And Their Relationship With Other Copd Treatmentsmentioning
confidence: 99%
“…59,60 A recent study confirmed cAMPmediated CFTR up-regulation by dual PDE3/4 inhibitors in human bronchial epithelial cells expressing wild-type CFTR or F508del CFTR. 56 Previously, Lambert et al had described restoration of CFTR function with a PDE4 inhibitor alone in human bronchial epithelial cells exposed to cigarette smoke; this effect was greater when the PDE4 inhibitor was associated to a CFTR potentiator (Ivacaftor). 61,62 Finally, PDE 4 inhibitors can enhance ciliary function, possibly through effects on CFTR activity.…”
Section: Mucus Production Ciliary Function and Airway Clearancementioning
confidence: 99%